SISTEM KERJA GOVERNOR DI PLTA PARAKANKONDANG SUMEDANG - Kiki Mulyadi (PROCEEDING STIMA)
Hydroelectric power plant is one of the power plants that use renewable in the form of water. The hydroelectric system converts the energy from the flowing water into mechanical energy and then into electrical energy. Water flows through a rapid pipe (Penstock) through a waterwheel or turbine where water will hit a blade that causes a waterwheel or turbine to spin.Governor is a system used to stabilize turbine rotation, at PT. Indonesia Sagulling Power UP The Parakan Hydro Power Unit Sub Unit has a nominal rotation speed of 600 rpm. 600 rpm was taken because the number of poles in the Parakan hydropower plant is 10 poles and the governor system must be able to stabilize the rotation to 600 rpm because the turbine rotation will affect the generator output frequency by adjusting the opening of the Guide Vane, the blades that surround turbine. And the speed drop owned by parakankondang hydropower is 3% with a reduced frequency of 1.5 Hz and a change of 0.1 Hz will cause a change in the load of 0.13 MW.